Re-emergence of Diphtheria. A Case Report in a Pediatric Emergency at a Tertiary Care Hospital in Karachi - Khurram Shaikh, Uzma; Bashir, Muhammad Arsalan; Laila, Saba; Kazi, Unaisa (Pakistan Journal of Medical & Health Sciences, 2024)
SUMMARY Diphtheria, caused by Corynebacterium diphtheria, is an acute bacterial infection that primarily affects the respiratory system. With the availability of diphtheria vaccines, the incidence of the disease has significantly decreased globally. However, in recent times, there has been a concerning resurgence of diphtheria in various parts of the world, including Pakistan, and hence presents a unique and pressing public health challenge, as evidenced by our case study exclusively reported from the pediatric emergency department. The study highlights the importance of early recognition and management of diphtheria cases and the need for booster doses in the EPI program to prevent this deadly disease re-emergence.